PERANCANGAN KAPAL GENERAL CARGO 7400 DWT KECEPATAN 11 KNOT DENGAN RUTE PELAYARAN TELUK BAYUR (PADANG) - TANJUNG PRIOK (JAKARTA) - Muhammad Ahlan Ghazali, (2020)
The use of land transportation in shipping needs and plantation products sometimes hinders activities. Utilizing sea lanes as a larger and more efficient mode of transportation helps supply and demand. The ship is a sea transportation that can supply the needs of each region by sea. The design of ships capable of carrying a lot of regional commodity needs will facilitate the supply of goods to regions throughout the Indonesian archipelago in a large scale. The use of General Cargo ships in the supply of goods is chosen because the costs are relatively cheaper compared to container ships. In general, ports in Indonesia have storage warehouses compared to container terminals. The cargo loading system on General Cargo ships that can maximize storage space and maximum capacity is more value in the use of this ship as a mode of transportation for shipping goods. Goods shipped in General Cargo ship loads can vary. Starting from the type of bulk cargo until goods that are generally large-sized can be transported by General Cargo ships.